The Effect of External Focus of Attention Instruction and Autonomy Support on Learning of an Aiming Task in Mentally Retarded Children - Seyed Mohammadreza Mousavi; Nahid Shetab Boushehri; Rasool Abedanzadeh (University of Tehran, 2020)
The aim of this study was to investigate the effect of external focus of attention instruction and autonomy support on learning of an aiming task in mentally retarded children. Therefore, 48 children (age range: 10-14 years, mean age 11.81+1.2 years) were selected from all mentally retarded children of Ahvaz city by convenient sampling method. Participants performed 10 trials as a pretest and according to their scores of the pretest, they were assigned to four groups: external attention, autonomy support, external attention-autonomy support and control. The task consisted of throwing 100-gram beanbags into a goal that was mounted at a distance of 2 meters from the participants on the wall. Participants performed 40 trials including 5 blocks, 8 trials each block in the acquisition phase. 10 minutes after the last acquisition block, the participants performed 10 trials as the posttest. 48 hours after the acquisition phase, retention test (10 trials) was performed to examine the learning effects of the participants under the same conditions as the pretest. The data were analyzed by mix ANOVA 2×2×5 in the acquisition phase and two-way ANOVA 2×2 in the retention phase with SPSS22 at significance level of P≤0.05. The results showed that all four groups had a significant improvement in their performance during the practice blocks. The external attention+autonomy support group gained the best scores in the acquisition phase (P≤0.05). The external attention+ autonomy support group presented the greatest performance in the retention test (P≤0.05). Therefore, it is suggested that a combination of autonomy support and external attention should be used to improve the performance and learning of aiming in mentally retarded children.